Penerimaan dan tanggapan masyarakat terhadap sumber zakat harta yang diikhtilaf - Sanep Ahmad,; Hairunnizam Wahid, (Penerbit Universiti Kebangsaan Malaysia, 2005)
Various efforts have been taken to increase zakat revenue. Privatizing zakat collection through the establishment of Pusat Zakat as implemented by many states seem to be effective. In addition, zakat revenue may also be increased by widening zakat base especially on the .unconsensus wealth. (harta diikhtilaf ). This action is reasonably acceptable because many current economic activities are now capable of yielding good return. However it is still undecided what are the type of wealth to be zakated, how the zakat is to be calculated, and how individual will react to this action. In this regard this study attempts to examine the acceptance and perception of individual and further investigates the factors influencing individual.s acceptance on these matters. This study utilizes primer data collected throughout Malaysia and be analysed using descriptive analyses. The result shows that respondents awareness and willingness to pay zakat is promising. Besides, religious knowledge and education level are found to affect significantly the level of willingness to pay zakat